Endoscopic Methods for the Treatment of Nonvariceal Upper Gastrointestinal Hemorrhage - Z.W. Li; F. Urrutia; R. Wensel; A.B.R. Thomson (Canadian Journal of Gastroenterology)
In the l970s, diagnostic fibreoptic endoscopy became part of the standard practice for evaluation of gastrointestinal disease. In the 1980s, therapeutic fibreoptic endoscopy is emerging as standard therapy for many gastrointestinal diseases. As the already sophisticated technology continues to blossom, it promises to become even more a part of the management of an increasing number of gastroenterological problems. Endoscopy can provide both a specific diagnosis as well as an identification of the high risk subgroup of patients with either active bleeding, or a non bleeding visible vessel that might benefit from endoscopic treatment. At endoscopy, patients with active ulcer bleeding have either arterial spurting, oozing or oozing beneath an overlying clot. These have poor outcomes: for example, when a non bleeding visible vessel is identified, the chances for rebleeding are approximately 50% during the period of that hospitalization . With an overlying clot without oozing, where dark spots are noted, there is less than a 10% chance of rebleeding. There are certain limitations for endoscopic hemostatic therapy and there are a few bleeding ulcers with an artery too large to expect endoscopic success. The kind of treatment chosen will be dictated by the availability of the therapeutic modalities and the skill of the surgeon.